Lung lesions of non-vaccinated puppies affected by canine distemper virus - Feijóo, Gimena; Yamasaki, Kanji; Verdes, José M. (Brazilian Journal of Veterinary Pathology, 2019)
Canine distemper is an uncommon disease in vaccinated domestic dogs, but presents high incidence in South America due to the lack of widespread prevention measures. The purpose of this study is to describe histological lung lesions in non-vaccinated puppies affected by canine distemper virus (CDV). The lungs of 4 non-vaccinated puppies ageing 2 to 5 months that showed respiratory signs for about 15 days were examined. Interstitial pneumonia was histologically detected in one puppy, while the other 3 showed alveolar lesions such as edema, congestion and hemorrhage. To our knowledge, there are no previous reports of pulmonary disease without interstitial pneumonia in puppies diseased by CDV. The differences observed between puppies may relate to distinct passive immune states. Remarkably, characteristic inclusion bodies of CDV were only detected in alveolar epithelial cells and macrophages of the puppy with interstitial pneumonia.